Health Media Production in 2D Motion Graphics to Understand about Body Metabolism System before Weight Loss and Weight Loss with Low-Carb, High-Fat Diet or Ketogenic Diet - ทวีสุข, ลัทธสิทธิ์; รัตนมงคลพร, หทัยภัทร (Siam Communication Review, 2019)
The objective of this article is to describe the production of 2D Motion Graphics about metabolic system before being on diet and Ketogenic diet losing weight method. The data were collected from medical documents and the author’s direct experience in Ketogenic diet losing weight. The concepts of Sign, Cartoon code, Representation, Biological Symbiosis and Colors were applied to produce this creative work, and distributed the work in Youtube, Facebook of TigerNoy Tv Channel